COVID-19: Emergence, Spread, Possible Treatments, and Global Burden - Keni, Raghuvir; Alexander, Anila; Nayak, Pawan Ganesh; Mudgal, Jayesh; Nandakumar, Krishnadas (Frontiers in Public Health, 2020)
The Coronavirus (CoV) is a large family of viruses, known to cause illnesses ranging from the common cold to acute respiratory tract infection. The severity of the infection may be visible as pneumonia, acute respiratory syndrome, and even death. Until the outbreak of SARS, this group of viruses whereas greatly overlooked. However, since the SARS and MERS outbreaks, these viruses have been studied in greater detail, propelling the vaccine research, an ongoing phenomenon in this direction. On December 31, 2019, mysterious cases of pneumonia were detected in the Wuhan city in China’s Hubei Province. On 7th January 2020, the causative agent was identified as a new coronavirus (2019-nCoV), and the disease was later named as COVID-19 by the WHO. The virus spread extensively in the Wuhan region of China and gained entry to over 29210 countries. Though experts suspected that the virus is transmitted from animals to humans, there are mixed reports on the origin of the virus. There are no treatment options available for the virus as such, limiting to the use of antiviral agents used for HIV/AIDS and other antiviral agents such as Remdesivir and Galidesivir. For the containment of the virus, it is recommended to quarantine the infected and to follow good hygiene practices. The virus has had a significant socio-economic impact globally. Economically, China is likely to experience a setback due to the pandemic along with the added trade war pressure more than other countries, which we have discussed in this paper.